Uncovering Justice as a New Dimension of Islamic Leadership: A Hybrid Systematic Literature Review and Bibliometric Analysis - Syamsul Hadi; Jain Yassin; Utik Bidayati; Alifah Widya Rachmawati (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2026)
A multitude of inquiries have explored Islamic leadership over the past few decades. Nevertheless, the academic literature on this topic remains limited. Therefore, the present investigation seeks to conduct an organized academic assessment, combined with a bibliometric evaluation, of Islamic leadership, anchored in currently available observational data. This study employs a structured literature review as its primary investigative framework, using the keyword phrase